2004
DOI: 10.2202/1548-923x.1075
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the At-Risk Challenge: Empowering Nursing Students Through Mentoring

Abstract: Wanting to improve student retention, progression, and graduation, the nursing faculty of the University of Nevada, Las Vegas developed a program for undergraduate students. Designated faculty mentors are available for academically at-risk students, or any student wanting to improve learning skills. Through mentoring sessions, students are helped to assess their learning difficulties, develop individualized prescription plans for learning, gain support during implementation of learning strategies, and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Since there are similarities between nursing programs and ATPs, the most common practices identified by nursing programs to improve student retention might prove beneficial to athletic training students, faculty, and administrators. The nursing literature has suggested that improving public knowledge of the nursing profession, 17 providing students with peer study sessions, 18,19 socializing students early on in their educational career, 19,20 and providing students with a mentoring program [19][20][21] can improve retention rates. Further, retention initiatives data suggest that persistence likely occurs when a student has access to services that promote meaningful learning opportunities, 22 which in general education refers to tutoring programs, writing centers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since there are similarities between nursing programs and ATPs, the most common practices identified by nursing programs to improve student retention might prove beneficial to athletic training students, faculty, and administrators. The nursing literature has suggested that improving public knowledge of the nursing profession, 17 providing students with peer study sessions, 18,19 socializing students early on in their educational career, 19,20 and providing students with a mentoring program [19][20][21] can improve retention rates. Further, retention initiatives data suggest that persistence likely occurs when a student has access to services that promote meaningful learning opportunities, 22 which in general education refers to tutoring programs, writing centers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing programs have developed student orientation seminars (Campbell & Dickson, 1996) and student faculty mentoring sessions (Candela, Kowalski, Cyrkiel, & Warner, 2004) for at-risk students. These orientation sessions help socialize students into the nursing program and faculty mentoring sessions assist students in defining their difficulties and developing strategies to help them overcome their challenges and persist in the program.…”
Section: Student Retention In Nursing Programs Is Relevant To Atepsmentioning
confidence: 99%
“…Improving public knowledge of the AT profession (Wells, 2003), providing students with peer study sessions (Higgins, 2004;Lockie & Burke, 1999), socializing students early on in their educational career (Candela et al, 2004;Lockie & Burke, 1999), and providing students with a mentoring program (Candela et al, 2004;Lockie & Burke, 1999;Matteson-Kane & Clarren, 2003) have the potential to translate to athletic training education. It remains unknown if ATEPs use any of these initiatives or any other programs to help reduce student attrition.…”
Section: Student Retention In Nursing Programs Is Relevant To Atepsmentioning
confidence: 99%
“…Asians and Hispanics will increase 5% and 6%, respectively, during the same period (Tiedt & Tiedt, 2002). By 2010, a third of the population will be ethnic minorities, and foreign-born residents will be at an all-time high of 24.8 million (Candela, Cyrkiel, Kowalski, & Warner, 2004). Eight percent of the population will have a language other than English as their primary language (Weise, 2006).…”
Section: Definition and Characteristics Of Multicultural Educationmentioning
confidence: 99%